Ergothioneine Improves the Quality of Boar Sperm During In Vitro Liquid Preservation by Regulating Mitochondrial Respiratory Chain - Qing Guo; Xue Liu; Yang Li; Ye Cheng; Jingchun Li (Animals)
Porcine artificial insemination primarily utilizes liquid-preserved (17 °C) semen; however, the quality of sperm diminishes progressively with extended preservation time. Ergothioneine (EGT) is a mitochondria-targeting antioxidant. Therefore, this study aimed to analyze the effect of various concentrations of EGT (0, 0.15, 0.3, and 0.6 mM) on the quality of boar sperm during in vitro liquid preservation and elucidate the underlying mechanisms of the mitochondrial electron respiratory chain inhibitor ROT. The results demonstrated that the addition of 0.3 mM EGT to the modified Modena extender significantly improved sperm motility and kinetic parameters, as well as mitochondrial membrane potential (MMP), adenosine triphosphate (ATP), antioxidant capacity, and the integrity of both the sperm plasma membrane and acrosome. Additionally, ROT significantly inhibited sperm motility, kinetic parameters, MMP, ATP levels, antioxidant capacity, and sperm integrity of the plasma membrane and acrosome. However, these adverse effects could be partially mitigated by the addition of 0.3 mM EGT. In conclusion, the novel findings of this study indicated that EGT plays a crucial role in protecting sperm from oxidative damage by regulating the mitochondrial electron respiratory chain, suggesting that the use of EGT is a promising approach for enhancing the in vitro liquid preservation efficiency of boar semen at 17 °C.